2020
DOI: 10.3390/toxins12010046
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Effects of T-2 Toxin on Primary Hepatic Cell Culture Models of Chickens

Abstract: Trichothecene mycotoxins such as T-2 toxin cause severe problems for agriculture, as well as for veterinary medicine. As liver is one of the key organs in metabolism, the main aim of our study was to investigate the immunomodulatory and cytotoxic effects of T-2 toxin, using primary hepatocyte mono-culture and hepatocyte—nonparenchymal cell (predominantly Kupffer cell) co-culture models of chicken. Cultures were exposed to 10 (T10 group), 100 (T100 group) and 1000 (T1000 group) nmol/L T-2 toxin treatment for 8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 41 publications
2
13
0
Order By: Relevance
“…In the present study, based on the results of the CCK-8 assay, the aerobe catabolic activity of the cultured cells moderately decreased after applying both inhibitors MI432 and MI460 in certain concentrations for 4 h. However, the extent of the reduction indicated that the inhibitors were not cytotoxic, in line with a previous study in which T-2 toxin caused a similar decline in the metabolic activity of the same cell culture models without being cytotoxic [ 25 ]. Following the longer, 24 h incubation, no significant differences were observed between control and MI-treated cells anymore, suggesting the rapid metabolic adaptation of liver cells to the applied MIs.…”
Section: Discussionsupporting
confidence: 89%
“…In the present study, based on the results of the CCK-8 assay, the aerobe catabolic activity of the cultured cells moderately decreased after applying both inhibitors MI432 and MI460 in certain concentrations for 4 h. However, the extent of the reduction indicated that the inhibitors were not cytotoxic, in line with a previous study in which T-2 toxin caused a similar decline in the metabolic activity of the same cell culture models without being cytotoxic [ 25 ]. Following the longer, 24 h incubation, no significant differences were observed between control and MI-treated cells anymore, suggesting the rapid metabolic adaptation of liver cells to the applied MIs.…”
Section: Discussionsupporting
confidence: 89%
“…The major metabolic pathways of T-2 include hydroxylation, hydrolysis, deepoxidation, and conjugation ( Figure 5 ) [ 153 ]. The typical metabolites of T-2 in human and animals are HT-2 toxin (HT-2), neosolaniol (NEO), 3′-OH-T-2, 3′-OH-HT-2, T-2 triol, T-2 tetraol, and some C12,13-deepoxy products [ 99 , 154 ].…”
Section: Biotransformation Of Mycotoxinsmentioning
confidence: 99%
“…There is only limited data available related to this issue; however, it would be an essential basis for future studies concerning the in vitro testing of anti-inflammatory agents. The applied 2D primary hepatocyte-non-parenchymal cell co-cultures of chicken origin have already been used in previous studies to investigate the cellular effects of acute heat stress and T-2 toxin [24,44]. Furthermore, even inflammatory models were designed using similar cultures of porcine origin [45].…”
Section: Discussionmentioning
confidence: 99%